Suicide Risk Assessment in Australian Emergency Departments: Assessing Clinicians' Disposition Decisions. (7th April 2014) - Weiland, T. J.; Cotter, A.; Jelinek, G. A.; Phillips, G.
Abstract : Objective . To determine (1) the uniformity of disposition decisions made by clinicians working in Australian emergency departments (EDs) using vignettes describing patients presenting with deliberate self-harm or suicide risk; (2) factors associated with these decisions; (3) factors associated with confidence in these decisions. Methodology . We validated and distributed by email an online survey tool to Australian emergency clinicians via their colleges. Participants were presented with five vignettes and asked to rate the level of risk and protective factors for suicide, the patient's disposition (admit/discharge/review), factors influencing this decision, their confidence in the decision, and factors that would have improved their confidence. Results . Percentages of participants choosing the modal disposition decision for each scenario ranged from 58.6% (136/232) to 92.4% (220/238), demonstrating uniformity in clinicians' disposition decisions. Predictors of disposition were consistently level of risk factors perceived and, infrequently, clinician factors including age and years experience. Confidence in disposition decisions was high across scenarios. Clinicians reported patient, clinician, contextual and decision support factors relevant to an Australian emergency context affected their disposition decisions and confidence in decisions. Conclusion . Emergency clinicians are uniform and confident in their disposition decisions for patient vignettes where there is risk of suicide or self harm.